Ruby in the Dust. Poetry and History in Padmāvat by the South Asian Sufi Poet Muhammad Jāyasī - de Bruijn, Thomas (Leiden University Press, 2012)
This book presents an innovative reading of the Indian mystical romance Padmāvat (1540). It describes the semantic polyphony of Jāyasī's seminal work from the perspective of the poet's role in the literary field, as mediator between the interests of his spiritual and worldly patrons. The contextual outlook of De Bruijn's interpretation corrects the identification with modern, nationalist notions of Hindu and Muslim identity that have dominated readings of Padmāvat until now. De Bruijn's reading reveals the confluence of poetry and history that inspired the many retellings of the tale of Padmāvatī and Ratansen in Persian and other Indian languages.